The Polymorphic Gene of Single Nucleotide Polymorphism (SNP) of Phytoene Synthase (PSY) to Characterize Carotenoids Yellow Root Cassava - Kurniawati, Siti; Hartati, N. Sri; Hartati, Hartati; Sudarmonowati, Enny (Jurnal ILMU DASAR, 2020)
Cassava (Manihot esculenta Crantz.) is a carbohydrate sources containing a limited amount of micronutrients, but some genotypes contain β-carotene as the precursor of vitamin A in the storage roots and leaves. Improvement of β-caroteneand minerals such as Fe / Zn content of cassava’s nutrition is mostly through by biofortification program. The storage root of β-carotene recognized by a yellow or yellowish color while the apical shoots with red to purplish. β-carotenein carotenoid biosynthetic pathway is an expression of the phytoene synthase (PSY) gene. The MePSY2 gene, one of the three MePSY family is the key gene to characterize carotenoids related gene in cassava. In this study, sequencing of the two cassava fulllenght PSY genomic DNA was carried out in conserved areas in the PSY gene region (PSY1 and PSY2) from the DNA of the cassava leaves. Adira1, Carvita25 and Ubi Kuning are yellow root storage genotypes (K1, K2 and K3) while Adira4 and Menti are white root storage genotypes (P1 and P2). Carvita25 is induced somaclonal variant of the Adira4 genotype. Contiq and consensus of nucleotide base sequences from the five cassava genotypes and CM3306-4 cultivars (acc GU111715.1) as references were analysed using the lasergene DNASTAR sequence analysis program. The results of the alignment of the base sequence constituent of the MePSY2 gene showed that the PSY2 gene with amplified genome length was 2,380 base pairs (bp) consisting of 1,140 bp exon region and 1,240 bp intron region. In the conserved coding region, there was a difference of one nucleotide base, that is, base C in two white tuber cassava genotypes replaced with A in three yellow tuber cassava genotypes in the 1.485 base (C1.485A). The SNP converts the amino acid (aa) alanine (A) to aspartic acid (D) at the 191th (A191D). Single Nucleotide polymorphism in conserved coding region can be used further as carotenoid marker for plant breeding of yellow root cassava. Keywords: β carotene, PSY gene, polymorphic gene SNP, yellow root cassava.